Pengaruh Pendidikan Kesehatan terhadap Pengetahuan dan Pencegahan Vaginitis pada Remaja SMK Rajawali - Budi Rustandi; Theophylia Melisa Manumara; Agni Noviani; Sevie Nuraini; Nayla Nurkhairun Nisa; Mesi Lestari; Risa Ismaya; Selvina Selvina; Kheisya Permana Putri; Nadiah Maratu Solihah; Meita Zeta Zetira; Siti Fatimatu Jahra Nurazijah; Arin Aulia Sabrina; Moch Rifki Mubarok (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Vaginitis is a common reproductive health issue among adolescent girls and can affect their health and quality of life. A lack of knowledge regarding reproductive health, genital hygiene and infection prevention are factors contributing to the high incidence of vaginitis among adolescents. Various studies indicate that a lack of good personal hygiene practices can increase the risk of reproductive tract infections. Findings indicate that health education delivered through various methods, such as audiovisual media, educational videos, leaflets, peer groups, and digital applications, can improve adolescents’ knowledge, attitudes, and behaviours regarding the maintenance of reproductive organ hygiene. It was found that poor genital hygiene practices are significantly associated with an increased incidence of vaginitis. Health education delivered in a structured and continuous manner has been shown to help adolescents understand the importance of maintaining reproductive health and adopting appropriate preventive behaviours. Therefore, health education needs to be continuously developed and integrated into school activities to support improvements in adolescent girls’ reproductive health and reduce the risk of vaginitis.